2019
DOI: 10.3390/ani9121091
|View full text |Cite
|
Sign up to set email alerts
|

Using Principles from Applied Behaviour Analysis to Address an Undesired Behaviour: Functional Analysis and Treatment of Jumping Up in Companion Dogs

Abstract: The aim of this study was to investigate the feasibility and effectiveness of procedures successfully used in human related applied behaviour analysis practices to the field of clinical animal behaviour. Experiment 1 involved functional analyses to identify the reinforcement contingencies maintaining jumping up behaviour in five dogs. Experiment 2 comprised teaching dog owners a noncontingent reinforcement intervention (i.e., time-based reinforcement) via behavioural skills training. Single-case experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 117 publications
1
15
0
Order By: Relevance
“…SCRMs are closely associated to the behavior analytic approach [ 82 ]. Thus, the small number of SCRM studies identified here further supports the notion that there is an overall lack of behavior-analytic research in the applied animal behavior change arena [ 83 ], including the application of conditioned reinforcement across applied settings and species. Two earlier reviews on the use of conditioned reinforcement in the animal behavior realm reached similar conclusions (e.g., clicker training [ 40 , 41 ]).…”
Section: Discussionsupporting
confidence: 55%
“…SCRMs are closely associated to the behavior analytic approach [ 82 ]. Thus, the small number of SCRM studies identified here further supports the notion that there is an overall lack of behavior-analytic research in the applied animal behavior change arena [ 83 ], including the application of conditioned reinforcement across applied settings and species. Two earlier reviews on the use of conditioned reinforcement in the animal behavior realm reached similar conclusions (e.g., clicker training [ 40 , 41 ]).…”
Section: Discussionsupporting
confidence: 55%
“…This raises the question of whether a particular enrichment is truly beneficial if it is not directly linked to a decrease in these undesirable behaviors. In fact, some authors recommend that prior to the onset of an environmental enrichment intervention, a complete evaluation be carried out through a functional behavior assessment (FBA) [95] to identify the events contributing to the origin and maintenance of clinically relevant behavior [96,97]. Despite its potential benefits, FBA is still seldom used in applied animal welfare science with non-human primates.…”
Section: Discussionmentioning
confidence: 99%
“…However, coming full circle, researchers are now successfully adapting and using behavioral protocols developed for use with people to impact animal welfare. For example, functional analysis protocols have been used to assess and treat problem behaviors in animals [87][88][89][90][91][92][93][94][95][96], and this function-based approach that emphasizes the identification and modification of existing behavior-environment relationships may help provide a framework that allows animal caregivers both a deeper understanding of behavior and the ability to move beyond the reliance of artificial reinforcers when modifying behavior [61]. In addition, empirical preference assessments have been successfully used in a variety of species [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] with promise for improving training effectiveness.…”
Section: The Future Of Behavior Analysis In Zoosmentioning
confidence: 99%